Infographics Development for Secondary School Students in English Learning - Kadek Nesya Febi Pramesti; I Gusti Ayu Lokita Purnamika Utami; Made Hery Santosa (Universitas Lambung Mangkurat, 2021)
This study aimed to develop infographics as teaching media for 7th students of grade secondary school in learning English. The method used in this study was Design and Development research (DnD) promoted by Richey and Klein (2005) which consist three steps, namely design, development, and evaluation. Initial observation had been done at one of junior high school in North Bali. In that observation, it was found the use of visual media in teaching still monotonous. The visual media that used in the teaching and learning process were only PowerPoint and videos from YouTube. The PowerPoint was mostly used in the teaching and learning activity. The PowerPoint slides were filled with many words related to the material. The teacher only explained the material through PowerPoint without doing other learning activities. The development of infographics was done to support the teacher in using visual media in teaching and learning process. The data collections of this study were carried out by library research, document analysis, and expert judgment. The data analysis of this study used mixed qualitative and quantitative research. The result of this study was infographics are very good media for teaching English to 7th grade junior high school. The design in each infographics was simple and effective as visual media for English teaching and learning activity. The quality of infographics was assessed using expert judgment by two experts. The result of expert judgment was the infographics media were classified as good media and did not need to be revised based on level accomplishment from Agung (2013). Teachers were expected to use various visual media in the class for creating fun and meaningful learning process. The infographics became complementary teaching media and can be used for a long time period.